KEBIJAKAN HUKUM PIDANA DALAM MENANGGULANGI TINDAK PIDANA LINGKUNGAN MENGENAI DAMPAK PEMBANGUNAN VILLA TERHADAP LINGKUNGAN - Teguh Andenoworeh, R.B Sularto, Untung Sri Hardjanto (Diponegoro Law Journal, 2012)
Bogor regency government uses preventive and repressive efforts to overcome the establishment of illegall villa. Preventive effort in the form of counseling, unannounced inspections (Sidak), and the provision of warning letters are kind of these efforts, while repressive effort is by wrecking the illegal villa. The necessity of criminal law policy is as a means to overcome the environmental crime. The policy of criminal law in the enforcement of environmental law, namely the necessity for criminal law policy as a means to overcome the environmental crime. The use of criminal law is as a part of a policy or political criminals which is adopted and used in Indonesia and also as the ground of an integral part to protect the society and to achieve the welfare society. Also it needs an improvement in environmental law, especially in the local regulations. In this study, the author gives a case of establishment of illegal villa which was occurred in Bogor regency and was processed by the court